Low Thermal Stress and Instant Efficient Atomization of Narrow Viscous Microfluid Film Using a Paper Strip Located at the Edge of a Surface Acoustic Wave Atomizer - Yulin Lei; Yusong Li; Jia Ning; Yu Gu; Chenhui Gai; Qinghe Ma; Yizhan Ding; Benzheng Wang; Hong Hu (Micromachines, 2025)
A traditional SAW (surface acoustic wave) atomizer directly supplies liquid to the surface of the atomized chip through a paper strip located in the path of the acoustic beam, resulting in irregular distribution of the liquid film, which generates an aerosol with an uneven particle size distribution and poor directional controllability, and a high heating phenomenon that can easily break the chip in the atomization process. This paper presents a novel atomization method: a paper strip located at the edge of the atomizer (PSLEA), which forms a micron-sized narrow liquid film at the junction of the atomization chip edge and the paper strip under the effect of acoustic wetting. By using this method, physical separation of the atomized aerosol and jetting droplets can be achieved at the initial stage of atomizer startup, and an ideal aerosol plume with no jetting of large droplets, a uniform particle size distribution, a vertical and stable atomization direction, and good convergence of the aerosol beam can be quickly formed. Furthermore, the effects of the input power, and different paper strips and liquid supply methods on the atomization performance, as well as the heating generation capacity of the liquid in the atomization zone during the atomization process were explored through a large number of experiments, which highlighted the advantages of PSLEA atomization. The experiments demonstrated that the maximum atomization rate under the PSLEA atomization mode reached 2.6 mL/min initially, and the maximum thermal stress was 45% lower compared with that in the traditional mode. Additionally, a portable handheld atomizer with stable atomization performance and a median aerosol particle size of 3.95 μm was designed based on the proposed PSLEA atomization method, showing the great potential of SAW atomizers in treating respiratory diseases.